Vehicle Routing Problem by Combining Nearest Neighbour and Local Search - Kurnia Iswardani; Ira Aprilia; Dwi Putri K (UJMC (Unisda Journal of Mathematics and Computer Science), 2023)
PT. X is a company tasked with distributing Elpiji Gas to major agents. The problem under study is to find a more optimal distribution route so it can maximize the use of other resources, for example the number of trucks used. This distribution problem will be solved by a combination two methods, Nearest Neighbor and Local Search with the hope of getting the shortest route. The way the Nearest Neighbor method works is selecting the Agent's location based on the shortest distance from the last location and improving the solution using Local Search (intra-route insertion (1-0)) by moving one customer's position in one route so that a good distribution route is produced